NÖROPATİK DAVRANIŞSAL AĞRI MODELLERİNDE HUMANİNİN AĞRI EŞİĞİ, OKSİDATİF STRES VE İNFLAMATUAR SİTOKİNLER ÜZERİNE ETKİLERİNİN İNCELENMESİ - BİLGİN, BATUHAN (Fırat Üniveristesi, 2022)
Nöropatik ağrının siyataljiye, diyabete ve kemoterapik ajan kullanımına bağlı gelişebileceği bilinmektedir ve bunlara bağlı gelişen ağrılı nöropatilerin patofizyolojisinde mitokondriyal disfonksiyonun, reaktif oksijen türlerindeki (ROS) ve inflamatuar sitokinlerdeki artışın rolü olabileceği yapılan çalışmalarla ortaya konmuştur. Ancak mitokondriyal türevli bir peptid olan humaninin nöropatik ağrıda etkisi bilinmemektedir. Bu tez çalışmasında başlıca amaç, metabolik (streptozotosin/STZ), toksik (oksaliplatin/OXA) ve travmatik (siyatik sinir kronik konstriksiyon hasarı/SKH) olmak üzere 3 farklı tip nöropatik ağrı oluşturulmuş fare modelinde humanin ağrı davranışı üzerine etkisini incelemekti. Bu tez çalışmasının bir diğer amacı ise nöropatik ağrı patofizyolojisinde rol oynayan oksidatif hasar ve inflamatuar sitokin seviyeleri üzerine humaninin etkisinin olup olmadığının irdelenmesi idi. Ayrıca STZ indüklü nöropatik ağrı modelinde humaninin etkisinin endojen opioid sistem aracılığıyla olup olmadığıda araştırıldı. Bu tez çalışmasında 3 farklı etiyolojiye sahip nöropatik ağrı oluşturulmuş farelere 15 gün boyunca humanin (4 mg/kg) uygulandı ve ağrı eşiğini değerleri hot plate, cold plate ve Von Frey testleri ile birer gün aralıklarla sıra ile ölçüldü. Bu ölçümler 30 dakika aralıklarla 240 dakika boyunca gerçekleştirildi. Humanin uygulamaları takiben hayvanlar dekapite edildi ve serumda total antioksidan (TAS), süperoksit dismutaz (SOD), katalaz (CAT), glutatyon (GSH), malondialdehit (MDA), nikotinamid adenin dinükleotit fosfat (NADPH), total oksidan (TOS), interlökin-1? (IL-1?) , interlökin-6 (IL-6) ve interlökin-10 (IL-10) seviyeleri enzime bağlı immünosorbent testi (ELISA) ile incelendi. STZ, OXA ve SKH ile nöropatik ağrı oluşturulmuş hayvanlarda yapılan 3 farklı ağrı davranışı testinde, humaninin 15 gün boyunca ağrı eşiğini istatistiksel olarak anlamlı düzeyde arttırdığı tespit edildi (P<0.05). Aynı zamanda humanin antioksidan enzim seviyeleri (TAS, SOD, CAT, GSH ve NADPH) artırırken (P<0.01), oksidan enzim seviyelerini (TOS ve MDA) azalttığı belirlendi (P<0.01). Humanin bu çalışmada ölçülen proinflmatuar sitokinleri azaltırken, anti inflamatuar sitokini artırdı (P<0.01). Bunun yanı sıra STZ indüklü nöropatik ağrıda humaninin antihipersensitif etkisine endojen opioid sistemin aracılık ettiği belirlendi. Bu tez çalışmasının sonuçları, STZ, OXA ve SKH kaynaklı nöropatik ağrıda mitokondriyal türevli peptid olan humaninin terapötik potansiyelini göstermektedir ve ayrıca bu potansiyel etkide oksidatif stres ile inflamatuar sitokinlerin rolünün anlaşılmasına katkı sağlayacaktır.

It is known that neuropathic pain may develop due to sciatica, diabetes and the use of chemotherapeutic agents, and studies have shown that mitochondrial dysfunction, increase in reactive oxygen species (ROS) and inflammatory cytokines may play a role in the pathophysiology of painful neuropathies that develop due to these. However, the effect of humanin, a mitochondrial-derived peptide, on neuropathic pain is unknown. The main purpose of this thesis study was to examine the effect of humanin on pain behavior in mice models with 3 different types of neuropathic pain: metabolic (streptozotocin/STZ), toxic (oxaliplatin/OXA) and traumatic (sciatic nerve chronic constriction injury/SCI). Another aim of this thesis study was to examine whether humanin has an effect on oxidative damage and inflammatory cytokine levels, which play a role in the pathophysiology of neuropathic pain. In addition, it was investigated whether the effect of humanin in the STZ-induced neuropathic pain model was mediated by the endogenous opioid system. In this thesis study, mice with neuropathic pain of 3 different etiologies were administered humanin (4 mg/kg) for 15 days and pain threshold values were measured sequentially with hot plate, cold plate and Von Frey tests at one-day intervals. These measurements were performed at 30-minute intervals for 240 minutes. Following humanin treatments, animals were decapitated and serum serum total antioxidant (TAS), superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), malondialdehyde (MDA), nicotinamide adenine dinucleotide phosphate (NADPH), total oxidant (TOS), interleukin -1? (IL-1?), interleukin-6 (IL-6) and interleukin-10 (IL-10) levels were analyzed by enzyme-linked immunosorbent assay (ELISA). In 3 different pain behavior tests performed in animals with neuropathic pain caused by STZ, OXA and SCI, it was determined that humanin increased the pain threshold statistically for 15 days (P<0.05). At the same time, it was determined that while humanin increased antioxidant enzyme levels (TAS, SOD, CAT, GSH and NADPH) (P<0.01), it decreased oxidant enzyme levels (TOS and MDA) (P<0.01). While humanin decreased the proinflammatory cytokines measured in this study, it increased the anti-inflammatory cytokines (P<0.01). In addition, it was determined that the antihypersensitive effect of humanin in STZ-induced neuropathic pain was mediated by the endogenous opioid system. The results of this thesis study show the therapeutic potential of humanin, a mitochondrial-derived peptide, in neuropathic pain caused by STZ, OXA and SCI, and will also contribute to the understanding of the role of oxidative stress and inflammatory cytokines in this potential effect.
Investigation of the effects of humanin on pain threshold, oxidative stress and inflammatory cytokines in neuropatic behavioral pain models
Keywords: Biyofizik